2018
DOI: 10.1049/iet-rpg.2016.0192
|View full text |Cite
|
Sign up to set email alerts
|

Development of a real‐scale cooling module for a PV power plant

Abstract: The goal of this study is to develop units of a photovoltaic (PV) cooling system and evaluate its performance, aiming at commercial electricity production, once the increase in electricity output is obtained by cooling down the temperature of the PV module. The methodology covers the description of production procedures, control and verification of three different models of the cooling system, of which two are sheet-and-tube types, with different diameters of coil curvature (85 and 140 mm), and one is a multi-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 18 publications
0
6
0
2
Order By: Relevance
“…Additionally, in order to maximize heat transfer, the mean distance between the heat generation and the collectors should be minimum. Another suggestion regarding the area in which the liquid flows on the PV cell, this shall be as large as possible in order to cover the whole surface [22]. For this application, van Helden et al [6] suggested a configuration with multiple channels that allow PV cells arranged in series to be cooled equally.…”
Section: Water-based Pvt Collectormentioning
confidence: 99%
“…Additionally, in order to maximize heat transfer, the mean distance between the heat generation and the collectors should be minimum. Another suggestion regarding the area in which the liquid flows on the PV cell, this shall be as large as possible in order to cover the whole surface [22]. For this application, van Helden et al [6] suggested a configuration with multiple channels that allow PV cells arranged in series to be cooled equally.…”
Section: Water-based Pvt Collectormentioning
confidence: 99%
“…Research in this area has focused on various aspects of solar panels, namely new shapes, orientation, cooling and ideal tilt angle of solar panels, with or without tracking [13][14][15][16][17]. The studies reviewed before indicated that most majority of the mirror panel configurations increased energy production.…”
Section: Introductionmentioning
confidence: 99%
“…There are numerous researches in the field of enhanced extraction of solar power from an existing system and the same is visible from the literature which includes the development of new maximum power point tracking algorithms, solar tracking methods, array reconfigurations, cooling, orientation and optimal tilt angle of the solar panel, suitable selection of different inverter topologies and the use of non-tracked mirror augmented PV systems [7][8][9][10][11][12][13]. All the above schemes will be feasible only if they are able to guarantee lower investment cost with high system efficiency.…”
Section: Introductionmentioning
confidence: 99%